Can right ventricular endomyocardial biopsy predict left ventricular fibrosis beforehand in dilated cardiomyopathy? - Kisaki Amemiya; Taka‐aki Matsuyama; Hatsue Ishibashi‐Ueda; Yoshiaki Morita; Manabu Matsumoto; Keiko Ohta‐Ogo; Yoshihiko Ikeda; Yasumasa Tsukamoto; Norihide Fukushima; Satsuki Fukushima; Tomoyuki Fujita; Kinta Hatakeyama (ESC Heart Failure, 2024)
Abstract Aims Myocardial fibrosis of the left ventricle (LV) is a prognostic factor in dilated cardiomyopathy (DCM). This study aims to evaluate whether fibrosis of right ventricular (RV) endomyocardial biopsy (EMB) can predict the degree of LV fibrosis beforehand in DCM. Methods and results Fibrosis extent in 70 RV‐EMB specimens of DCM diagnosis was compared with that in the whole cross‐sectional LV of excised hearts in the same patients (52 explanted hearts for transplant and 18 autopsied hearts). The median interval between biopsy and excision was 4.1 (0.13–19.3) years. The fibrosis area ratio of the EMBs and excised hearts were evaluated via image analysis. The distribution of cardiovascular magnetic resonance–late gadolinium enhancement (LGE) in the intraventricular septum was classified into four quartile categories. The fibrosis area ratio in RV‐EMB correlated significantly with that in the short‐axis cut of the LV of excised hearts (r = 0.82, P < 0.0001) and with a diffuse pattern of LGE (r = 0.71, P = 0.003). In a multivariate model, after adjusting for the interval between biopsy performance and heart excision, the fibrosis area ratio in RV‐EMB was associated with that in LV‐excised heart (regression coefficient, 0.82; 95% confidence interval, 0.68–0.95; P < 0.0001). Conclusions The fibrosis observed in RV‐EMB positively correlated with the extent of fibrosis in the LV of excised hearts in patients with DCM. The study findings may help predict LV fibrosis, considered a prognostic factor of DCM through relatively accessible biopsy techniques.